2021
DOI: 10.1007/s12551-021-00817-6
|View full text |Cite
|
Sign up to set email alerts
|

Ras isoform-specific expression, chromatin accessibility, and signaling

Abstract: The anchorage of Ras isoforms in the membrane and their nanocluster formations have been studied extensively, including their detailed interactions, sizes, preferred membrane environments, chemistry, and geometry. However, the staggering challenge of their epigenetics and chromatin accessibility in distinct cell states and types, which we propose is a major factor determining their specific expression, still awaits unraveling. Ras isoforms are distinguished by their C-terminal hypervariable region (HVR) which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 197 publications
(287 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, the InterPro server was used to identify the locations of these SNPs on NRAS protein domains, and the analysis found that all SNPs, except rs1658971260 SNP, were located on the important, small GTP-binding protein domain. This domain is responsible for catalytic activity and contains sites of nucleotide binding and effector interactions ( Omerovic et al, 2007 ; Nussinov et al, 2021 ). Therefore, mutations in this region are expected to affect the protein function and its binding properties.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the InterPro server was used to identify the locations of these SNPs on NRAS protein domains, and the analysis found that all SNPs, except rs1658971260 SNP, were located on the important, small GTP-binding protein domain. This domain is responsible for catalytic activity and contains sites of nucleotide binding and effector interactions ( Omerovic et al, 2007 ; Nussinov et al, 2021 ). Therefore, mutations in this region are expected to affect the protein function and its binding properties.…”
Section: Discussionmentioning
confidence: 99%
“…Titin (TTN), a connectin, is megadalton-sized filamentous molecule that promotes human trophoblast invasiveness via the activation of the MAPK pathway, providing proper placentation and embryo development [42]. NRAS belongs to the family of Ras proteins, which control cell proliferation pathways, cell growth, and division [43]. Tropomodulin-3 (Tmod3) negatively regulates cell motility by controlling actin polymerization and stability, and in the case of Tmod3 knockdown, the gradual increase in the level of cytoplasmic actin and spin- It is important to note that the protein products of several analyzed target genes are polyfunctional, i.e., they participate in more than one biological process indicated in Figure 12.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to sparseness of data, such single cell transcriptomics are technically highly challenging; entries are missing, and they are noisy. Structural networks may not be able to distinguish between isoforms whose sequences (thus structures) are highly similar, yet have different functions, as discussed earlier for Rac1 versus Rac3, or K-Ras4B versus e.g., N-Ras or H-Ras, or splice isoform K-Ras4A ( Muratcioglu et al., 2017 ; Nussinov et al., 2016a ; Nussinov et al., 2021e ), or Rap1A versus Rap1B ( Nussinov et al., 2020 ). Posttranslational modification, degradation, and other forms of regulation are also important factors.…”
Section: Perspectivementioning
confidence: 99%